2016
DOI: 10.1097/ccm.0000000000001282
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm Disruption in the Critically Ill

Abstract: Circadian disruption often demonstrates serial degradation: initially, the amplitude attenuates along with delayed circadian phase. With increasing acuity of illness, circadian rhythmicity may be lost entirely. Causes of chronodisruption may be environmental or internal to the patient. In particular, inadequate daytime illumination and nocturnal light pollution disrupt healthy circadian periodicity. Internal causes of circadian arrhythmia include critical illness itself and subjective experience of distress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
84
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 102 publications
2
84
0
3
Order By: Relevance
“…This phenomenon in patients with an acute stroke might be caused by cerebral dysregulation and associated with reduced perfusion, hypoxia, and disturbed neurotransmitters (Maldonado, 2008). Especially delirium during the night is discussed by disturbed melatonin circulation (Oldham, Lee, & Desan, 2016) and might explain the result of a delirium only during the night. Another hypothesis might be early infections during onset of stroke causing delirious episodes, for example, by aspiration and first cerebral responses, especially in patients with poststroke immunodepression (Famakin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon in patients with an acute stroke might be caused by cerebral dysregulation and associated with reduced perfusion, hypoxia, and disturbed neurotransmitters (Maldonado, 2008). Especially delirium during the night is discussed by disturbed melatonin circulation (Oldham, Lee, & Desan, 2016) and might explain the result of a delirium only during the night. Another hypothesis might be early infections during onset of stroke causing delirious episodes, for example, by aspiration and first cerebral responses, especially in patients with poststroke immunodepression (Famakin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of delirium is unknown, sleep disruption has been thought to contribute to ICU delirium. These patients often have altered sleep patterns due to environmental noise, abnormal lighting, and overuse of sedating medications …”
mentioning
confidence: 99%
“…It has been shown that critically ill patients with sleep deprivation have a disrupted circadian rhythm and decreased melatonin production . Exogenous melatonin is being evaluated as a potential agent to restore sleep patterns and help prevent and/or treat delirium in hospitalized patients . Previous studies have demonstrated that the administration of nightly low‐dose exogenous melatonin to elderly patients in hospital wards resulted in a lower incidence of delirium .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, emergency rooms and intensive care units (ICUs) need constant lighting to monitor the health of patients. Because severe disruption of the circadian clock and sleep loss affect many processes, such as the immune response, hormone secretion, and mental ability, exposure to constant light ultimately impairs the recovery of patients in the ICU1314. Limiting the use of LAN, therefore, is not the solution for these kinds of problems.…”
mentioning
confidence: 99%